Ernest goes to camp Ernest goes to jail - Cherry, John (John R.); Sams, Coke; Williams, Stacy; Varney, Jim; Mill Creek Entertainment; Buena Vista Home Entertainment (Firm) (United States : Mill Creek Entertainment, 2011)
Ernest goes to camp: Ernest P. Worrell, handyman at Kamp Kikakee, achieves his greatest ambition and becomes a camp counselor--to a gang of juvenile delinquents from the Midstate Boys Detention Center.
Ernest goes to jail: Only a bumbling bank janitor like know-it-all Ernest P. Worrell could serve on a jury and end up serving time in jail in place of the criminal.
Ernest goes to camp screenplay by John Cherry, Coke Sams ; produced by Stacy Williams ; directed by John Cherry ; Ernest goes to jail directed by John Cherry ; produced by Stacy Williams ; screenplay by Charlie Gale and Coke Sams.
Ernest goes to camp: Previously released as a motion picture in 1987.
Ernest goes to jail: Previously released as a motion picture in 1990.
Ernest goes to camp ; screenplay by John Cherry, Coke Sams ; produced by Stacy Williams ; directed by John Cherry.
Ernest goes to jail ; written by Charlie Cohen ; produced by Stacy Williams ; directed by John Cherry.
Jim Varney.
MPAA rating: PG.
Keywords: Worrell, Ernest P. (Fictitious character) -- Drama; Camp counselors -- Drama; Juvenile delinquents -- Drama; Mistaken identity -- Drama; Lawyers -- Corrupt practices -- Drama; Criminals -- Drama; Demonology -- Drama; Comedy films; Drama; Feature films; Fiction films